Seeds of hope, bereavement, and loss activity book : helping children and young people cope with change through nature - Jay, Caroline, 1953- (Jessica Kingsley Publishers, 2015)
This activity book uses nature as a gentle way of helping children aged 5+ understand change, loss and death. Through creative activities such as making a paper memory tree, writing and drawing about feelings, and looking closely at nature, children learn about natural changes and how to cope with and express feelings of grief.